Research on Viterbi Decoding Algorithm in the Washback Effect of Language Testing - Zhang, Yuejun (2022 International Conference on Artificial Intelligence and Autonomous Robot Systems (AIARS), 2022)
Language testing is a scientific method for detection, analysis and diagnosis of a language. In linguistic research, it belongs to the high-level language system. Viterbi algorithm is currently the most widely used and effective compilation method, which has the advantages of high efficiency and speed in the system. For this reason, this paper focuses on the application of Viterbi decoding algorithm in the washback effect of language testing system. The purpose of the research here is to analyze the washback effect of the algorithm on language testing and to propose new insights. The methods used in this article include text analysis method and questionnaire survey method. Through these methods, the Viterbi decoding algorithm and its application in the washback effect of language testing are studied accordingly. The survey results show that 20% of students and 11% of teachers believe that the washback effect of language testing has a positive effect, and the Viterbi decoding algorithm has a digital translation effect, so its application in the system is relatively meaningful.